Ideological and Physical Education Integration in Higher Education: Strategies for Mental Health Education - Deng Shaoliu; Li Tongbai, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
From the actual situation and results of the people across the country working together to fight the epidemic since the outbreak of the epidemic, this article proposes the current focus of physical education in colleges and universities, namely the theory of socialism with Chinese characteristics, core values, and Chinese spirit. When major events occur in society, ideological work must respond quickly. At present, the ideological work of college graduates is at an important stage. Under the current epidemic situation, strengthen the physical work of college students, strengthen scientific guidance, strengthen humanistic care, and actively participate in the anti-epidemic work to ensure that college students can have a correct ideological system and a positive attitude. Mentality in the face of the epidemic. Based on the current situation of the epidemic and the changes in college students' ideology, psychology and values, the article puts forward the opportunities and challenges for the development of college students' ideological work under the current situation. And further discuss the possibility of reform theoretically and methodically, so as to further improve the quality of teaching and work, and provide new ideas for the ideological education work in colleges and universities.